1987
DOI: 10.1139/y87-154
|View full text |Cite
|
Sign up to set email alerts
|

Surface pH and the control of intracellular pH in cardiac and skeletal muscle

Abstract: Both surface pH (pHs) and intracellular pH (pHi) were measured using single- and double-barreled pH-sensitive microelectrodes in isolated sheep cardiac Purkinje strands, rabbit and cat papillary muscle, and mouse and rat soleus muscle. Superfusion of the preparations with a relatively low buffered solution (containing 5 mM HEPES buffered to control pH) causes surface acidosis that correlates with efflux of metabolically produced acids in the unstirred layer of fluid surrounding the tissue. Acidification of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…Several studies have provided histochemical (Ridderstråle, 1979;Lönnerholm, 1980;Riley et al 1982;Dermietzel et al 1985;Decker et al 1996), biochemical (Wetzel & Gros, 1990 and functional evidence (Zborowska-Sluis et al 1974;Effros & Weissman, 1979;Geers et al 1985;De Hemptinne et al 1987) for a membrane-bound, sarcolemmal carbonic anhydrase (CA) in skeletal muscle. Waheed et al (1992) have demonstrated that in rat skeletal muscle the sarcolemmal CA is a 39 kDa, glycosylated, phosphatidylinositol-glycan anchored CA IV.…”
Section: _1mentioning
confidence: 99%
“…Several studies have provided histochemical (Ridderstråle, 1979;Lönnerholm, 1980;Riley et al 1982;Dermietzel et al 1985;Decker et al 1996), biochemical (Wetzel & Gros, 1990 and functional evidence (Zborowska-Sluis et al 1974;Effros & Weissman, 1979;Geers et al 1985;De Hemptinne et al 1987) for a membrane-bound, sarcolemmal carbonic anhydrase (CA) in skeletal muscle. Waheed et al (1992) have demonstrated that in rat skeletal muscle the sarcolemmal CA is a 39 kDa, glycosylated, phosphatidylinositol-glycan anchored CA IV.…”
Section: _1mentioning
confidence: 99%
“…Finally, it is worth considering whether alteration of the extracellular buffering capacity and hence of the pH at the immediate surface of the preparation influences the pH, transients and steady-state values in the presence and nominal absence of C02-HCO3-(see de Hemptinne, Morranne & Vanheel, 1987). Increased intracellular acid loading and hence acid extrusion in the nominal absence of C02-HCO3-may lead to a lower surface pH and hence contribute to the slower recovery and lower steady-state pHi.…”
Section: Na+-h+ Exchangementioning
confidence: 99%
“…15 - 16 It is a routine finding even in normal well-superfused tissue and is due to the inability of diffusion and extracellular buffers to control pH in the presence of this continuing efflux of acid equivalents. 17 It is known to vary directly with the size of the preparation and the metabolic rate and to vary inversely with the external pH buffer capacity. 16 - 17 The measurement is useful in that changes in pH, can indicate changes in the cell metabolism.…”
Section: Dresdner Et Al Canine Purklnje Cell Ph After Myocardial Infamentioning
confidence: 99%
“…16 - 17 The measurement is useful in that changes in pH, can indicate changes in the cell metabolism. 17 - 18 However, it is also a required measurement for the calculation of the true transmembrane H + gradient, which cannot be determined from the difference in pH| and the bath pH (pH b ) alone.…”
Section: Dresdner Et Al Canine Purklnje Cell Ph After Myocardial Infamentioning
confidence: 99%